2023
DOI: 10.1126/sciadv.adf2966
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-catalyzed carboxylation of aromatic C─H bonds with CO 2

Abstract: The carboxylation of nonactivated C─H bonds provides an attractive yet hitherto largely elusive chemical process to synthesize carboxylic acids by incorporation of CO 2 into the chemical value chain. Here, we report on the realization of such a reaction using simple and nonactivated arenes as starting materials. A computationally designed Pd(II) complex acts as organometallic single-component catalyst, and apart from a base, necessary for thermodynamic stabilization of the intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…63 A similar process was discovered for the traditional palladium-catalyzed carboxylation with CO 2 to prepare aromatic carboxylic acids. 64,65 Finally, D was reduced by one electron from Ir(II) to generate Pd(0), which then proceeded to the next catalytic cycle. Subsequently, aryl carboxylate which underwent further acidification resulted in the formation of aromatic carboxylic acids.…”
Section: Visible-light-driven Oxidative Addition and Reductive Elimin...mentioning
confidence: 99%
“…63 A similar process was discovered for the traditional palladium-catalyzed carboxylation with CO 2 to prepare aromatic carboxylic acids. 64,65 Finally, D was reduced by one electron from Ir(II) to generate Pd(0), which then proceeded to the next catalytic cycle. Subsequently, aryl carboxylate which underwent further acidification resulted in the formation of aromatic carboxylic acids.…”
Section: Visible-light-driven Oxidative Addition and Reductive Elimin...mentioning
confidence: 99%
“…One must note, however, that it cannot be excluded completely, that unexpected side reactions may be accessible in an experimental system which might not have been envisioned or possibly overlooked in the prior computational work. Computational studies of this kind have demonstrated their potential to narrow down significantly the plethora of choices an experimentalist could make with the potential of predictive catalyst design for example for olefin hydrogenation, 16 decarboxylative Heck-type coupling 13 and direct insertion of CO 2 14,15 into arenes.…”
Section: Computational Details and General Approachmentioning
confidence: 99%
“…In this work we use computationally guided catalyst design for the identification of suitable catalyst systems which bases on DFT computations following an approach which has been used earlier by us and was successfully transferred to experimental chemistry. 13–16…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Leitner’s group reported the use of a Pd II complex as an organometallic single-component catalyst for the simple and non-activated direct carboxylation of aromatic C–H bonds with CO 2 . The reaction requires no additives other than the base required to stabilize the intermediate product and turnover numbers of ≤10 2 , and high regioselectivities are achieved . However, due to the challenges of the inertness and selectivity of C–H bonds, the direct carboxylation of aryl C–H bonds with CO 2 still has defects such as a narrow substrate range, a large catalyst loading, and harsh reaction conditions .…”
Section: Introductionmentioning
confidence: 99%